Prenylated flavonoids and total extracts from Morus nigra L. root bark inhibit in vitro growth of plant pathogenic fungi. (3rd September 2017) - Simonetti, G.; Brasili, E.; D′Auria, F. D.; Corpolongo, S.; Ferrari, F.; Pasqua, G.; Valletta, A.
Abstract: Total extracts and kuwanon G from Morus nigra root bark showed antifungal activity against several phytopathogenic fungi, with minimal inhibitory concentration (MIC50 ) ranging from 32 to 128 μg/ml and from 16 to 64 μg/ml, respectively. Acetonic extracts inhibited 60% B. cinerea biofilm formation at concentration of 128 μg/ml.